Level of Readiness to Become Entrepreneurs Among Lifelong Learning Programmes Participants in Malaysian Community Colleges - Abd Samad, Noorazman Bin; Ghazalan, Mohd Shahzuan Bin; W Ahmad, W Mohd Rashid Bin; Ismail, Affero Bin; Harun, Hairuddin Bin; Ismail, Mohd Erfy Bin; Amiruddin, Mohd Hasril Bin; Razali, & Nizamuddin Bin (Journal of Technical Education and Training, 2019)
An entrepreneur needs to be physically and mentally prepared, with creative thinking skills, risk taker attitudes, as well as being a wise decision maker. Individuals aiming to be successful entrepreneurs need to have adequate entrepreneurial readiness with respect to knowledge, interests, motivation and abilities. The purpose of the research is to measure the level of readiness towards becoming entrepreneurs among participants of the lifelong learning programme in Malaysian community colleges. This research focuses on four elements of readiness comprising knowledge, interest, motivation and ability which were measured using a self-perception questionnaire. The sample for this research consisted of 236 participants from 305 students in the Lifelong Learning (LL) programme for Pastry making at Malaysian community colleges under the Ministry of Education. Data were analysed using mean and Kruskal Wallis test. The data analyses results show that the level of readiness from the aspect of knowledge (M = 3.67, SD = 0.58) is moderate, interest (M = 4.13, SD = 0.55) is high, motivation (M = 4.13, SD = 0.55) is high and ability (M = 3.8852, SD = 0.64) is moderate. No difference was found on entrepreneurial readiness between participants of different age groups indicating that age may not be a contributing factor towards entrepreneurship among pastry making LL programme participants.